2005
DOI: 10.1055/s-2005-858198
|View full text |Cite
|
Sign up to set email alerts
|

Vergleichende computertomographische und kernspintomographische Beurteilung von Wirbelsäulenverletzungen der BWS und LWS anhand der Magerl-Klassifikation

Abstract: Classification of spine injuries according to the Magerl-classification showed a significant agreement between CT and MRI and therefore a comparable evaluation of stability. MRI was superior in delineating ligamental lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
0
0
2
Order By: Relevance
“…The results showed that out of 46 fractures, only 5 received a different classification based on CT images compared to MR images. MR imaging revealed more bone lesions and detected the ligamentum longitudinal rupture in 5 patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that out of 46 fractures, only 5 received a different classification based on CT images compared to MR images. MR imaging revealed more bone lesions and detected the ligamentum longitudinal rupture in 5 patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…Die Diagnostik degenerativer Prozesse bildet heutzutage neben der Frakturdarstellung, die der CT mittlerweile ebenbürtig geworden ist, sowie dem Nachweis entzündlicher oder neoplastischer Veränderungen eine der Hauptindikationen zur lumbalen MRT [22,23]. (Modic-)Signalveränderungen der kartilaginären Endplatten und des angrenzenden Knochenmarks werden dabei relativ häufig beobachtet [9,14,16], wobei eine klare Assoziation zur degenerativen Bandscheibenerkrankung belegt wurde [10,13,24].…”
Section: Diskussionunclassified
“…Darüber hinaus ist die Sensitivität für ossäre Läsionen bei der MRT hçher als bei der CT. Die MRT ist deshalb die wichtigste Methode zur Untersuchung akuter Rückenmarkverletzungen [3]. Obwohl die MRT der CT in der Diagnostik traumatischer Rü-ckenmarkverletzungen überlegen ist, wird sie häufig erst nach Tagen durchgeführt, weil der Patient zunächst oft intensivmedizinisch betreut wird.…”
unclassified